Sedimentation rate of trace elements in the surface sediment of the south China Sea - Che Abd Rahim Mohamed,; Noor Azhar Mohamed Shzili, (Universiti Kebangsaan Malaysia, 2000)
Trace elements contents in the surface sediments (about 5 cm depth) of the South China Sea were obtained during the Ekspedisi Matahari cruises. Their concentrations are slightly different from cruise to cruise and may be related to the content of water column and input from the land through river or wind. The range of accumulation rates of the heavy metals are also wide; 3.80 23.7 mg.cm2/kyr,8.89 - 24.7 mg.cm2/kyr, 3.78 - 14.4 mg.cm2/kyr and 20.1 30 mg.cm2/kyr for Cu, Ni, Pb and Zn, respectively. The metal/Fe ratios are slightly same with the preindustrial period and probably controlled by natural inputs from water column.